Effect of nano and micro SiO2 weight percent on interlaminar fracture toughness of woven roving/ epoxy composites - Jaafer, Harith I. (Iraqi Journal of Physics, 2012)
Effect of nano and micro SiO2 particles with different weight percent (2,4,6,8 and 10) %wt on the Interlaminar fracture toughness (GIc) of 16-plies of woven roving glass fiber /epoxy composites prepared by hand lay – up technique were investigated. The specimens were tested using DCB test (mode I).Area method was used to compute the interlaminar fracture toughness. The results show that, GIc would increase with the increasing in the filler content, the main failure in microcomposites and nanocomposites was delamination in the layers, the delamination reduced with increasing in the filler content.